EFFECT OF ADDING DIFFERENT LEVELS OF TAMARIND PULP TO DRINKING WATER IN PRODUCTIVE PERFORMANCE FOR BROILER - & Ibrahim, Tarif (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This study was conducted at the poultry farm Animal Production Department, College of Agriculture, University of Baghdad, Abu Ghraib, for the period from 19/9/2016 to 30/10 / 2016. (42 days) The object of this study was effect of adding different levels of tamarind pulp (0, 5, 15, 25 g / L ) to the drinking water on productive traits of broiler chicken. A total of 120 unsexed Ross 308, one day old, an initial weight 41.5 g was used in the experiment. Chicks were fed on starter diet for the  first three weeks of age and finisher diet for the 4,5 and 6 weeks of age. Birds were distributed to four treatments, The first T0 control (without any addition), The second T5, third T15 and fourth T25 treatment added tamarind pulp in the drinking water in concentrations 5, 15 and 25 g / L drinking water respectively. The results indicated that the use tamarind pulp in drinking water in concentration 5 g / L water led to Significant improvement (P